EFEK TERAPI PISANG TONGKA LANGIT (Musa troglodytarum) TERHADAP INDEKS ERITROSIT MENCIT (Mus musculus) MODEL MALARIA - Efraim Samson (Scripta Biologica, 2019)
Malaria is an infectious disease that is still a major health problem in various countries, including Indonesia. Malaria parasite infection can induce changes in structure, physiology and biochemistry in hematology causing damage to erythrocytes. The use of plants in malaria treatment (phytotherapy) began to be developed at this time. Tongka langit banana (Musa troglodytarum) is one type of banana that has the potential to be developed. This study aimed to see the therapeutic effect of tongka langit banana against the erythrocyte index of mice with malaria models. The results showed that the therapy of tongka langit banana was able to increase the erythrocyte index (RBC, MCV, MCH, and MCHC) in mice with malaria, and the most effective dose is 0.75 gr/mice/day.Key Words: Tongka Langit Banana, Erythrocyte Index, Phytotherapy, Malaria.